Avaliação da eficácia do Programa Nacional de Assistência Estudantil (PNAES) na Universidade Federal do Pará - MONTEIRO, Michele Elane de Sá (Universidade Federal do Pará, 2024)
In the last twenty years, there has been an expansion in the number of enrollments in undergraduate courses at the Federal Institutions of Higher Education (IFES), resulting from the implementation of a set of affirmative actions inserted in the Brazilian educational context. Affirmative actions led to a change in the profile of students entering the IFES, who began to carry out actions to support the permanence of this new public in the institutions, these actions are defined as student assistance. This is the context in which this research is located, which has the general objective of evaluating the effectiveness of the National Student Assistance Program (PNAES) at the Federal University of Pará (UFPA), taking the period from 2017 to 2021 as a cutout. The research presents in its theoretical framework discussions on the evaluation of public policies, student assistance and on the National Student Assistance Program within the scope of UFPA. With regard to methodological procedures, the research has an applied nature, with a qualitative approach, with exploratory - descriptive objectives, the case study was used as a research strategy. For data collection, a bibliographical and documental survey was carried out, semi-structured interviews with the five managers that make up the team that coordinates student assistance actions at UFPA, and questionnaires were applied to 48 students benefiting from the PNAES. The results of the research indicate that PNAES has been effective, the students assisted by the program have satisfactory academic performance, and data referring to retention or evasion was not identified among the students participating in the research. In addition, they indicate that although it has been identified within the scope of this research that the program has achieved the intended result, the UFPA institutionally does not carry out the evaluation of the program, with only occasional pedagogical evaluations. As a final product of the research, a draft proposal for monitoring and evaluating the PNAES at UFPA was proposed.